Big cities – ‘quiet places’: tracing relationships between material and immaterial qualities of urban spaces - Hanne Wiemann Nielsen; Gertrud Jørgensen; Ellen Braae (Spool, 2016)
This paper investigates the theme particular places from the perspective of ‘quiet places’, by examining potential links between material and immaterial qualities of four distinct typologies of urban spaces in the landscape metropolis, and offering five thematic lenses to sharpen our view for the particular. While the relationship between green spaces and restorative qualities for humans has long been acknowledged, the present research investigates other types of urban spaces, not focusing on ‘green’ or dB ratio as such but instead on confluences of soundscape, cityscape, flowscape, and other ‘scapes’ i.e. ‘material-immaterial landscapes’ in particular places in the two cities. This kind of particularity is an under-researched field also in methodological terms. We therefore set up a survey, in which we asked people about their appreciations of various material and immaterial qualities of the place; the conceptualisation of which derived partly from a pilot study and partly from a structured literature review. The responses revealed noticeable differences between the four typologies and less between similar types in the two cities. The results of the survey also showed a variety of expressions, deepening our understanding of the experienced qualities and simultaneously opening up for a new vocabulary addressing this interaction and its importance for ‘quiet places’, discussed in relation to methodological considerations.